Mapeamento das evidências das revisões sistemáticas do Grupo Anestesiologia da Colaboração Cochrane: entendendo seu valor para a prática clínica - Santos Junior, Reinaldo da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Cochrane Collaboration systematic reviews aim to offer updated, objective and consistent information for clinical practice and in order to settle Health policies. However, inconsistence of evidence, as well as inability of raising recommendations is being observed. The aim of this study is to analyze the systematic reviews of Cochrane Collaboration Anesthesia Group and to map its use for clinical practice and scientific research. Methods: A systematic study was conducted, having the analyzes of all systematic reviews of Cochrane Collaboration Anesthesia Group until February, 2014, and then validating which recommendation for clinical practice, based on the author’s conclusions, would be more suitable. Data are shown in percentage and 95% confidence interval (CI). Besides, the number of clinical assays and meta-analyzes per systematic review is demonstrated. Results: 115 systematic reviews were analyzed. There is enough evidence to support recommendation either with or without the need of more studies, as in 32.2% and 2.6% [CI 95% 23.7; 40.7], respectively. Evidences that were opposite to interventions, with or without the need of further studies, consisted in 6.1% [CI 95% 1.7; 10.4] and 1.7% [IC 95% 0; 4.0], respectively. Absence of evidence, with or without the need of other studies, was found in 57.4% [CI 95% 48.4; 66.4] e 0%, respectively. Of all, 95.7% of the reviews suggest that independently of the results, more studies are needed to be made. The average number of clinical assays in the reviews was 19.6, ranging from zero to 737, and the average number of meta-analyzes was 9.3, ranging from zero to 92. Conclusion: Most of the systematic reviews of Cochrane Collaboration Anesthesia Group results in lack of evidence or insufficient evidence in order to recommend interventions for clinical practice, thus highlighting the need of new controlled and randomized clinical studies

As revisões sistemáticas da Colaboração Cochrane visam oferecer informações atualizadas, objetivas e com evidências consistentes para a prática clínica e para o estabelecimento de políticas de saúde. Entretanto, verifica-se frequentemente uma inconsistência de evidências e incapacidade de gerar recomendações. O objetivo desse estudo foi analisar as revisões sistemáticas do Grupo Anestesiologia da Colaboração Cochrane e mapear sua utilidade para a prática clínica e para a pesquisa científica. Realizou-se estudo transversal com análise de todas as revisões sistemáticas publicadas no Grupo Anestesiologia da Colaboração Cochrane até fevereiro de 2014, verificando-se qual o tipo de recomendação para a prática clínica e para a pesquisa científica, por meio da análise das conclusões de seus autores. Os valores são apresentados em porcentagem e intervalo de confiança de 95%. Além disso, computou-se o número de ensaios clínicos e meta-análises por revisão sistemática. 115 revisões foram analisadas. Evidências que apoiam a intervenção, com recomendação para a realização de mais estudos ou sem recomendação para mais estudos: 32,2% [IC 95% 23,7; 40,7] e 2,6% [IC 95% 0; 5,5], respectivamente. Evidências contrárias a intervenção, com recomendação para realização de mais estudos ou sem recomendação para mais estudos: 6,1% [IC 95% 1,7; 10,4] e 1,7 [IC 95% 0; 4,0], respectivamente. Ausência de evidências, com recomendação para a realização de mais estudos ou sem recomendação para mais estudos: 57,4% [IC 95% 48,4; 66,4] e 0%, respectivamente. Do total, 95,7% das revisões sugerem a realização de mais estudos independentemente dos resultados obtidos. O número médio de ensaios clínicos nas revisões foi de 19,6, variando entre zero e 737 e o número médio de meta-análises foi igual a 9,3, variando entre entre zero e 92. A maioria das revisões sistemáticas do Grupo de ...
Keywords: Anestesiologia - Pesquisa; Meta-analises; Medicina baseada em evidências; Revisão; Estudos transversais; Evidence-based medicine